Fabrication Rapitest Luster Leaf Color Change-Based for Soil pH Measurement: Comparison Study. Issue 1 (1st February 2022) - Asriyani, N; Mufti, N; Zulaikah, S; Abadi, M T H
Abstract: Agricultural productivity is hindered by low soil fertility. One of the causes is the condition of pH levels on agricultural land. pH measurement can be done using Rapitest Luster Leaf based on discoloration. Rapitest fabrication uses a colorimetric method by mixing reagents and indicators. Rapitest is characterized using XRD, XRF, EDX, and FTIR. Rapitest has been fabricated compared to Rapitest Luster Leaf. Rapitest on soil pH measurement provides color indicator is deep red, orange to yellow, light green, and green. The color indicates when pH is 0-1 the solution is deep red, the pH is about 2-3 the solution is orange to yellow, the pH is about 3-4 the solution is light green, the pH is about 5-7 green. XRD analysis indicates both of Rapitest contain Barium Sulfate (BaSO4 ). Based on XRF testing, Barium content of 88% and Sulfate of 5.9%. The EDX results showed the rapitest content of fabrication results close to the reference result of Oxygen (O) 61.37 At%, Sulfur (S) 17.91 At%, and Barium (Ba) 20.72 At%. Based on FTIR results in the range of 1190 cm -1 indicate sulfonate. In the range 1055, 983, and 648 cm -1 indicate sulfate ion. In the range 698, 648, 597 cm -1 indicate disulfide. Based on the results of the analysis, Rapitest in this study have similarities to Rapitest Luster Leaf.